2016
DOI: 10.1016/j.envres.2015.11.020
|View full text |Cite
|
Sign up to set email alerts
|

The in vitro respiratory toxicity of cristobalite-bearing volcanic ash

Abstract: Ash from dome-forming volcanoes poses a unique hazard to millions of people worldwide due to an abundance of respirable cristobalite, a crystalline silica polymorph. Crystalline silica is an established respiratory hazard in other mixed dusts, but its toxicity strongly depends on sample provenance. Previous studies suggest that cristobalite-bearing volcanic ash is not as bio-reactive as may be expected for a dust containing crystalline silica. We systematically address the hazard posed by volcanic cristobalite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
51
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(59 citation statements)
references
References 40 publications
5
51
3
Order By: Relevance
“…In this study, assessment of the biological response from the triple cell co-cultures following VA exposures alone resulted in no significant ( p  > 0.05) cytotoxicity, changes in cellular morphology, oxidative stress or release of (pro-)inflammatory mediators (TNF-α and IL-8). Therefore, the findings of the initial dose-respose analysis of VA exposures alone are largely in congruence with previous research with Soufrière Hills ash [43, 46, 50]. …”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…In this study, assessment of the biological response from the triple cell co-cultures following VA exposures alone resulted in no significant ( p  > 0.05) cytotoxicity, changes in cellular morphology, oxidative stress or release of (pro-)inflammatory mediators (TNF-α and IL-8). Therefore, the findings of the initial dose-respose analysis of VA exposures alone are largely in congruence with previous research with Soufrière Hills ash [43, 46, 50]. …”
Section: Discussionsupporting
confidence: 86%
“…Yet, in the current study, it was observed that no significant differences in oxidative stress levels were evident in any of the combined particle exposures compared to the negative control. In light of these observations, DEP showed no deviation from the negative control but VA treatment increased the relative abundance of GSH, an observation previously attributed to increased production by macrophages (in monoculture) to cope with volcanic ash [46]. Therefore, comparatively, the effect of DEP on GSH levels is greater than the effect seen with VA alone, and the effects noted with the combined exposure scenario could be attributed to the DEP driving an oxidative stress environment in the cell cultures rather than the absence of any oxidative stress.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations